2021
DOI: 10.1177/09603271211053292
|View full text |Cite
|
Sign up to set email alerts
|

Diosgenin inhibits the proliferation of gastric cancer cells via inducing mesoderm posterior 1 down-regulation-mediated alternative reading frame expression

Abstract: Introduction Whether and how mesoderm posterior 1 (MESP1) plays a role in the proliferation of gastric cancer cells remain unclear. Methods The expression of MESP1 was compared in 48 human gastric cancer tissues and adjacent normal tissues. Knockdown of MESP1 was performed to investigate the role of MESP1 in the proliferation and apoptosis of BGC-823 and MGC-803 gastric cancer cells. Knockdown of alternative reading frame (ARF) was performed to study the role of ARF in the inhibitory effect of MESP1 knockdown … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…Diosgenin demonstrates an anticancer impact by suppressing the expression of mesoderm posterior 1 (MESP1) within gastric cancer cells. This action stimulates processes like cell proliferation, apoptosis, and overall growth inhibition [ 81 ].…”
Section: Secondary Metabolites From Solanaceaementioning
confidence: 99%
“…Diosgenin demonstrates an anticancer impact by suppressing the expression of mesoderm posterior 1 (MESP1) within gastric cancer cells. This action stimulates processes like cell proliferation, apoptosis, and overall growth inhibition [ 81 ].…”
Section: Secondary Metabolites From Solanaceaementioning
confidence: 99%
“…MESP1 belongs to the family of transcription factors and promotes the proliferation of GC cells by inhibiting the expression of ARF, which is a tumor suppressor in human cancer. Therefore, diosgenin could be a potential natural product for the treatment of GC [116]. Another hallmark involved in carcinogenesis is invasion and metastasis.…”
Section: Fenugreekmentioning
confidence: 99%
“…It could inhibit esophageal cancer cells proliferation, migration and invasion, and induce apoptosis with an optimal measure of 50 g/mL on Eca109. (24,25) Gastric Cancer Previous studies have shown that diosgenin have effects on human gastric adenocarcinoma cells mainly include BGC823, MGC803, SGC7901, MNK45 and AGS cells, which inhibited the proliferation, growth and invasion, promoted apoptosis of BGC823 and MGC803 gastric cancer cells, (26,27) inhibited the growth of MGC803 and SGC7901 cells and increased the apoptosis rate of MGC803 cells to 30.08% with the dosage at 60 μg/mL. (28) Furthermore, diosgenin caused a dose-dependent decrease in the AGS and SGC7901 cells viability, induced signifi cant increases in G 0 /G 1 cell cycle arrest and apoptosis.…”
Section: Antitumor Effects Of Diosgenin Digestive System Tumors Oral ...mentioning
confidence: 99%
“…(32,45) Diosgenin exerts anti-cancer effect through inhibiting mesoderm posterior 1 (MESP1) expression in gastric cancer cells, promotes the cell proliferation, apoptosis, and growth. (26) Increasing Level of ROS ROS are the main molecules produced by the body in the process of oxidative stress, and the accumulation of ROS in cells can lead to cell death. (30) A series of studies have shown that diosgenin strongly generated ROS and this oxidative stress might induce apoptosis through activation of ASK1, which are critical upstream signals for JNK/p38 MAPK activation in HepG2 cancer cells.…”
Section: Regulating Signal Pathwaymentioning
confidence: 99%